Method Development and Application of an Accelerated Solution Stability Screen for Drug Discovery. (December 2020) - Gomez-Sanchez, Ruben; Besley, Stephen; Zeliku, Zoe; Young, Robert J.
An important aspect to understand about an experimental molecule in drug discovery is its stability in solution. A compound that degrades might be eliciting its apparent effect via a degradation product, so it is important to understand the solution stability profile of a compound early on in the drug discovery process. Improvements and application of a streamlined, higher-throughput method for testing solution stability to support drug discovery are described. Mass spectrometry detection has been incorporated into the screen to allow for the identification of degradation products. The amount of compound needed for the assay has been significantly reduced using 10 mM DMSO solutions instead of solid material. The buffers used in the screen provide the stability-pH profile of compounds with additional variations to assess liabilities under oxidizing and reducing conditions. In this article, we discuss the method development, screen validation, guidelines for result interpretation, and results for a set of marketed drugs to illustrate the application of the screen.